Bimbingan Belajar Baca Al-Quran dalam Meningkatkan Hasil Belajar PAI Kelas VI SD Muhammadiyah Ambon - Kamaru, Fardin; Nufus, Hayati (COGNITIVISM: Journal of Educational Research and Development, 2025)
This study aims to improve the learning outcomes of PAI students in grade VI of SD Muhammadiyah Ambon. The subjects of this study are 6 people who were selected using the purposive sampling technique. Data was collected through observation, interviews, and documentation. Data analysis is carried out with stages of data reduction, and data interpretation. The results of this study found that the emergence of Qur'an reading guidance learning in SD Muhammadiyah Ambon was motivated by the school's efforts in developing an Islamic education system that is adapted to the development of science and technology and existing socio-cultural changes and can be one of the characteristics of SD Muhammadiyah Ambon. The goal to be achieved is to improve the fluency in mastering the Qur'an reading of SD Muhammadiyah Ambon and students are able to read the Qur'an fluently and correctly, the introduction of tajweed from the beginning to the end and perfection in mastering the makhorijul letters. The method used in learning Qur'an reading guidance at SD Muhammadiyah Ambon is assignment through the practice of reading and memorizing short letters in the Qur'an with emphasis on reading in terms of Makhorijul letters and tajweed through practice techniques. As for the approach used in the learning process of reading the Qur'an, it is using an individual approach